Neuroscience in science fiction films - Packer, Sharon (McFarland & Company, Inc., Publishers, 2015)
"As the gap between science fiction and science fact has narrowed, films that were intended as pure fantasy at the time of their premier have taken on deeper meaning. Examining the parallel histories of psychiatry, neuroscience and cinema, this book shows how science fiction films offer insightful commentary on the scientific and philosophical developments of their times"--